Activation of microlipophagy during early infection of insect hosts by Metarhizium robertsii. Issue 3 (4th March 2022) - Li, Bing; Song, Shuangxiu; Wei, Xuefei; Tang, Guirong; Wang, Chengshu
ABSTRACT: The requirement of macroautophagic/autophagic machinery for filamentous fungal development and pathogenicity has been recognized, but the underlying effects and mechanisms remain elusive. The insect pathogenic fungus Metarhizium robertsii infects hosts by cuticular penetration through the formation of the infection structure appressoria. Here, we show that autophagic fluxes were highly activated during the appressorial formation of M. robertsii . Genome-wide deletion of the autophagy-related genes and insect bioassays identified 10 of 23 encoded MrATG genes with requirements for topical fungal infection of insect hosts. Besides the defect in forming appressoria on insects (two null mutants), these virulence-reduced mutants were largely impaired in penetrating cellophane membrane and insect cuticles, suggesting their failures in generating proper appressorium turgor. We found that the conidial storage of lipid droplets (LDs) had no obvious difference between strains, but autophagic LD degradation was impaired in different mutants. After induction of cell autophagy by nitrogen starvation, we found that LD entry into vacuoles was unaffected in the selected mutant cells with potential failures in forming autophagosomes. The finding therefore reveals a microlipophagy machinery employed in this fungus and that the direct engulfment of LDs occurs without inhibition by the downstream defective lipolysis. Our data first unveil the activation and contribution of microlipophagy to fungal infection biology. The obtained technique may benefit future detection of microlipophagy in different organisms by examining vacuolar or lysosomal engulfment of LDs in core autophagic gene deletion mutants. Abbreviations : AIM: Atg8-family interacting motif; ATG: autophagy-related; CM: complete medium; CMAC: 7-amino-4-chloromethylcoumarin; DTT: dithiothreitol; ER: endoplasmic reticulum; GFP: green fluorescent protein; LD, lipid droplet; MM: minimum medium; MM-N: minimum medium without nitrogen source; PDA: potato dextrose agar; PMSF: phenylmethylsulfonyl fluoride; RFP: red fluorescent protein; SDB: Sabouraud dextrose broth; SDS-PAGE: sodium dodecyl sulfate-polyacrylamide gel electrophoresis; TAG: triacylglycerol; TEM: transmission electron microscopy; WT, wild type.